2020
DOI: 10.1063/1.5130485
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of MBE grown Mn4N on MgO, SiC, GaN and Al2O3 substrates

Abstract: Mn4N is a compound magnetic material that can be grown using MBE while exhibiting several desirable magnetic properties such as strong perpendicular magnetic anisotropy, low saturation magnetization, large domain size, and record high domain wall velocities. In addition to its potential for spintronic applications exploiting spin orbit torque with epitaxial topological insulator/ferromagnet bilayers, the possibility of integrating Mn4N seamlessly with the wide bandgap semiconductors GaN and SiC provides a path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The AHE of Mn 4 N films on semiconductors substrates have also been reported [61]. Figures 15(a)-(d) show the anomalous Hall resistance of all the films.…”
Section: Ahementioning
confidence: 79%
See 1 more Smart Citation
“…The AHE of Mn 4 N films on semiconductors substrates have also been reported [61]. Figures 15(a)-(d) show the anomalous Hall resistance of all the films.…”
Section: Ahementioning
confidence: 79%
“…The epitaxial growth of Mn 4 N films on SiC implies the potential for the application with wide bandgap semiconductors. In 2020, Zhang et al reported the structure and magnetic properties of Mn 4 N films on MgO, SiC, GaN and sapphire [61]. The crystal quality of Mn 4 N films was observed by RHEED.…”
Section: Magnetic Properties Of Mn 4 N Filmsmentioning
confidence: 99%
“…Instead of (001) orientation, 111-oriented films can be grown on various substrates, such as 6H-SiC [232] and GaN. [233][234][235] Judging from the nanoelectron-beam diffraction patterns, the superlattice structure of antiperovskite-type Mn 4 N crystal is evident, even when using a MgO(111) substrate. [236] Noncollinear magnetic structures are favored in the 111-oriented Mn 4 N films, efficient STT and/or SOT-induced magnetization switching can be expected for bilayer systems in accordance with previous work.…”
Section: Crystal Orientation Dependencymentioning
confidence: 99%
“…Recently, the strong correlation between magnetic anisotropy and inplane strain has been confirmed by growing Mn 4 N films on different substrates [32]. Besides, the structure and magnetic properties of Mn 4 N films on semiconductor grown by MBE have also been reported [33]. However, the magnetic and electronic transport properties of Mn 4 N films influenced by film thickness and temperature have remained confusing.…”
Section: Introductionmentioning
confidence: 99%